2019
DOI: 10.21203/rs.2.14516/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnoveterinary survey of medicinal plants used for treatment of animal diseases in Ambo District of Oromia Regional State of Ethiopia

Abstract: Background: Traditional knowledge on the use of medicinal plants is in danger of extinction because of different changes taking place all over the world including Ethiopia and thus there is a need for its immediate documentation for the purpose of conservation, sustainable utilization and development. Thus, an ethnobotanical study was conducted in Ambo District, Oromia Regional State of Ethiopia to document and analyze local knowledge on medicinal plants used for the treatment of animal diseases.Methods: Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…(25, 44, 51-57) Although the study area was rich in its plant resource, ethnoveterinary medicinal plants were scanty due to natural and anthropogenic factors mainly the conflict on using the resource by both people of afar and Tigray regional states who shares border of the forest compared to other studies conducted before. (26,27,(58)(59)(60)(61)(62)(63)(64) Exclusively, this current finding also documents two plant species (Verbascum sinaiticum & Schinus molle), which have a great importance in beekeeping management practices, by preventing bee swarm from bad odor. (Table-6) In this study, the highest number of plant species having ethnoveterinary medicinal value were found in Fabaceae (9, 16%) followed by Solanaceae (6, 11%) and Amaranthaceae (4, 7%) ( Table -1…”
Section: Diversity Of Ethnoveterinary Medicinal Plantsmentioning
confidence: 52%
See 1 more Smart Citation
“…(25, 44, 51-57) Although the study area was rich in its plant resource, ethnoveterinary medicinal plants were scanty due to natural and anthropogenic factors mainly the conflict on using the resource by both people of afar and Tigray regional states who shares border of the forest compared to other studies conducted before. (26,27,(58)(59)(60)(61)(62)(63)(64) Exclusively, this current finding also documents two plant species (Verbascum sinaiticum & Schinus molle), which have a great importance in beekeeping management practices, by preventing bee swarm from bad odor. (Table-6) In this study, the highest number of plant species having ethnoveterinary medicinal value were found in Fabaceae (9, 16%) followed by Solanaceae (6, 11%) and Amaranthaceae (4, 7%) ( Table -1…”
Section: Diversity Of Ethnoveterinary Medicinal Plantsmentioning
confidence: 52%
“…The major method of remedy preparation was pounding, 24(21%), followed by crushing, 13 (12%). Dissimilar patterns were reported by some ethnoveterinary studies(46,58,73) where pounding and crushing, (79.2%), crushing (62.7%) and chop and soak in water with salt overnight then squeezed, (97.8%) found that the main mode of preparations respectively. The majority 39(34%) of medicinal plants preparations were revealed to be administered orally, and 19 (17%) were administered dermal, 10(9%) taken topically.…”
mentioning
confidence: 52%
“…A large proportion of the remedies in the study district were prepared by crushing or squeezing, which could be attributed to its ease of processing. Other studies [18,31,33,40,64] conducted elsewhere in the country also reported crushing as the commonly used method in the preparation of remedies. Availability and its property in dissolving many active compounds could be the reasons for the common use of water as diluent in the preparation remedies in the district as it is also the case in other parts of the country [18,65,66].…”
Section: Parts Used and Methods Of Remedy Preparation And Routes Of Administrationmentioning
confidence: 98%
“…erefore, there is an urgent need for conducting more ethnoveterinary surveys in different parts of the country to save the traditional knowledge and the associated medicinal plants from further loss. Some ethnobotanical surveys have so far been conducted in the Oromia region of Ethiopia, including that in Borana [2], Bale Mountains National Park [4], Chiro district [5], the Dabo Hana district of Illubabor zone [6], four districts of Jimma zone [7], selected districts of East Wollega zone [8], Horro Gudurru district [9], Yabelo and Liben districts [10], the Melkabello district of East Hararghe zone [11], the Midakegn district of West Shewa zone [12], Eastern Shewa and Arsi zones [13], Kelem Wollega zone [14], the Dale Sadi district of West Hararghe zone [15], the Berbere district of Bale zone [16], Wolmera district [17], and Ambo district [18], with the purpose of documenting knowledge exclusively focused on medicinal plants used to control livestock ailments. However, to the knowledge of the authors, there is no study conducted in the Adea Berga district to document medicinal plants traditionally used to manage livestock ailments.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnoveterinary medicine has been practiced in different regions of the world, such as Benin [1], Brazil [2][3][4][5][6], Ethiopia [7][8][9], India [10-13], Italy [14], Kenia [15], Nepal [16], Nigeria [17], South Africa [18], Spain [19], Swiss [20], Trinidad and Tobago [21], Pakistan [22] and Uganda [23], to maintain health or treat illnesses of domestic animals. Regarding the targeted animal species, specific for pastoral people, ruminants have higher value and therefore are more often addressed for treatment in countries with this tradition [17;21;24-27].…”
Section: Introductionmentioning
confidence: 99%